Phase 1 and preclinical profiling of ESM‐HDAC391, a myeloid‐targeted histone deacetylase inhibitor, shows enhanced pharmacology and monocytopaenia. Issue 12 (11th July 2022) - Furze, Rebecca C.; Molnar, Judit; Parr, Nigel J.; Ahmad, Faiz; Henry, Yvette; Howe, David; Singh, Rajendra; Toal, Martin; Bassil, Anna K.; Bernard, Sharon G.; Davis, Robert P.; Gibson, Adele; et al.
Abstract : Aims: To improve the tolerability and therapeutic application of histone deacetylase inhibitors (HDACi), by application of an esterase‐sensitive motif (ESM), to target pharmacological activity directly to mononuclear myeloid cells expressing the processing enzyme carboxylesterase‐1 (CES1). Methods: This first‐in‐human study comprised single and multiple ascending dose cohorts to determine safety and tolerability. Pharmacodynamic parameters included acetylation, cytokine inhibition and intracellular concentrations of processed acid metabolite in isolated monocytes. Mechanistic work was conducted in vitro and in a CES1/Es1e lo mouse strain. Results: ESM‐HDAC391 showed transient systemic exposure (plasma half‐life of 21–30 min) but selective retention of processed acid for at least 12 hours, resulting in robust targeted mechanistic engagement (increased acetylation in monocytes plus inhibition of ex vivo stimulated cytokine production). ESM‐HDAC391 was well tolerated and clinical toxicities common to non‐targeted HDACi were not observed. ESM‐HDAC391 treatment was accompanied by the novel finding of a dose‐dependent monocyte depletion that was transient and reversible and which plateaued at 0.06 × 10 9 monocytes/L after repeat dosing with 20 or 40 mg. Characterisation of monocyte depletion in transgenic mice ( CES1/Es1e lo ) suggested that colony stimulating factor 1 receptor loss on circulating cells contributed to ESM‐HDAC‐mediated depletion. Further mechanistic investigations using human monocytes in vitro demonstrated HDACi‐mediated change in myeloid fate through modulation of colony stimulating factor 1 receptor and downstream effects on cell differentiation. Conclusion: These findings demonstrate selective targeting of monocytes in humans using the ESM approach and identify monocytopaenia as a novel outcome of ESM‐HDACi treatment, with implications for potential benefit of these molecules in myeloid‐driven diseases.